Estimating the Strength of Associations Between Prenatal Diet Quality and Child Developmental Outcomes: Results From a Large Prospective Pregnancy Cohort Study. Issue 11 (3rd August 2019) - Borge, Tiril Cecilie; Brantsæter, Anne Lise; Caspersen, Ida Henriette; Meltzer, Helle Margrete; Brandlistuen, Ragnhild Eek; Aase, Heidi; Biele, Guido
Abstract: Our aim in this study was to estimate the strength of associations between prenatal diet quality and child behavioral, language, and motor functions in the Norwegian Mother and Child Cohort Study (1999–2008). We created a prenatal diet quality index (PDQI) based on adherence to Norwegian dietary guidelines. Child outcomes were defined as sum scores on the Child Behavior Checklist, the Ages and Stages Questionnaire, and the Child Development Index at ages 18, 36, and 60 months. Using a longitudinal cohort study design and Bayesian hierarchical modeling, we estimated association strengths using inverse probability weighting to account for selection bias. In total, 27, 529 mother-child pairs were eligible for inclusion. A 1–standard-deviation increase in PDQI score was associated with an absolute reduction in outcome sum scores of 0.02–0.21 and a 3%–7% relative decrease, with larger decreases seen for language and motor functions than for behavioral functions. PDQI scores were inversely associated with all child functions, but the estimated strength of each association was low. The results indicate that the observed variations in PDQI scores in an industrialized Western society may not profoundly influence the child functions studied.